2013
DOI: 10.1289/ehp.1205575
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Particulate Air Pollution and Term Birth Weight: A Multi-Country Evaluation of Effect and Heterogeneity

Abstract: Background: A growing body of evidence has associated maternal exposure to air pollution with adverse effects on fetal growth; however, the existing literature is inconsistent.Objectives: We aimed to quantify the association between maternal exposure to particulate air pollution and term birth weight and low birth weight (LBW) across 14 centers from 9 countries, and to explore the influence of site characteristics and exposure assessment methods on between-center heterogeneity in this association.Methods: Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
244
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(272 citation statements)
references
References 34 publications
19
244
5
4
Order By: Relevance
“…Area-level socioeconomic status is controlled by census-tract median household income using data from the United States Census Bureau of 2000 for each census tract in Massachusetts. These covariates are consistent with the published literature on birthweight and particulate matter (Dadvand and others, 2013). Some studies also adjust for co-pollutant exposures, such as ozone, although the need for this may vary by region, where studies in the northeast have found similar effect sizes after this adjustment (Bell and others, 2007).…”
Section: Data Example: Association Between Air Pollution and Low Birtsupporting
confidence: 85%
“…Area-level socioeconomic status is controlled by census-tract median household income using data from the United States Census Bureau of 2000 for each census tract in Massachusetts. These covariates are consistent with the published literature on birthweight and particulate matter (Dadvand and others, 2013). Some studies also adjust for co-pollutant exposures, such as ozone, although the need for this may vary by region, where studies in the northeast have found similar effect sizes after this adjustment (Bell and others, 2007).…”
Section: Data Example: Association Between Air Pollution and Low Birtsupporting
confidence: 85%
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%
“…

PM2.5: Particulate matter less than 2.5 µm; PM10: particulate matter less than 10 µm; BS: black soot; CP: cardiopulmonary; RM: respiratory mortality. ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Probable, but not specified explicitly in the text; D External cost of energy to estimate the automotive pollution impact on health in Europe [81]; E Calculation based on the actual number of participants who changed mode from car to bicycle; F Estimated for hypothetical individuals who changed transport mode from car to bicycle; G Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; H Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach.

…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%